PERAN LAYANAN BIMBINGAN KARIER DALAM MEMBENTUK KESIAPAN KERJA SISWA - Faizatul Mufliha; Yuni Arfa; Widya Agustin; Nurhayati; Dwi Risma Siti Aisyah; Rusmiyati; Listiani (Universitas Muhammadiyah Metro, 2026)
This study examines the role of career guidance services in shaping students’ work readiness through a literature review approach. This topic is crucial as work readiness is influenced not only by academic achievement but also by career understanding, decision making skills, and psychological preparedness for entering the workforce. Therefore, career guidance services are considered a strategic component in helping students prepare for their future in a more directed and realistic manner. The purpose of this study is to identify and analyze the contribution of career guidance services to students’ work readiness based on previous research findings. The method used is a literature study by reviewing scientific articles, national and international journals, and other relevant sources published in recent years. The analysis process is conducted systematically by categorizing, comparing, and synthesizing findings related to the research topic. The results indicate that career guidance services play a significant role in improving self-understanding, career exploration, future planning, and students’ adaptability to workplace demands. In addition, the implementation of innovative and contextual service strategies has been shown to strengthen students’ employability competencies more effectively. This study contributes by providing a comprehensive understanding of the importance of optimizing career guidance services as a strategic effort to develop students’ work readiness sustainably.